Man Up but Stay Smooth: Hybrid Masculinities in Advertising for Men's Grooming Products. Issue 2 (June 2019) - Scheibling, Casey; Lafrance, Marc
In this article, we address the question of how masculinities are constructed in advertising for the burgeoning market of men's grooming products. We present findings from a thematic analysis of all grooming product advertisements found in Esquire magazine from 2011 to 2013. Based on the results, we emphasize the ways in which these ads construct "hybrid" and "flexible" masculinities through combining symbols and narratives relating to bodywork, power, heterosexuality, work, family, and nostalgia. While the constructions of masculinity we see in these ads are hybridized and flexible, we argue that men's grooming product advertising should be read as marketing a contemporary "crisis" of masculinity in the context of late-modern consumer culture.